Overt Hypothyroidism and Severe Growth Retardation in a Preschool Girl with Poorly Controlled Nephrotic Syndrome: Case Report and Literature Review - Joana Mikulevič; Karolina Tumelienė; Robertas Kemežys; Augustina Jankauskienė (Acta Medica Lituanica)
Background. Nephrotic children may develop thyroid hormone dysfunction due to urinary excretion of thyroid hormones. In contrast to the subclinical hypothyroidism that affects around 30% of children with nephrotic syndrome (NS), the patient in this case had overt hypothyroidism and severe growth retardation. Clinical case. A 5 years and 8 months old girl with steroid-dependent NS was referred from another center due to persistent edema and decreased diuresis, being treated with mycophenolate mofetil (MMF) 250 mg once a day and L-thyroxine 50 mcg daily since 4 months of NS onset because of hypothyroidism. Her albumin was 12.64 g/l, cholesterol 25.64 mmol/l and proteinuria 5 g/l. Severe growth retardation was observed: patient’s height was 93.5 cm (–13 cm <3 percentile), weighted 17.2 kg (15–25 percentile). Her disease vintage was over 3 years. Girl’s growth velocity has slowed down from 3.5 months. The patient received a high cumulative dose of prednisolone (approx. 7800 mg in 1 year and 8 months). Thyroid-stimulating hormone was higher (18.04 mU/L) with reduced FT4 11.43 pmol/l and IGF-1 < 15 µg/L. Kidney biopsy revealed minimal change disease, and genetic testing was negative. Intensive NS treatment with methylprednisolone pulse therapy, enlarged doses of MMF and albumin infusion were started and L-thyroxine dose was increased to 75 mcg. TPOAb was in normal range (12.65 IU/ml). After 3 weeks she was discharged with no edema and after stopping methylprednisolone treatment thyroid function normalized and L-thyroxin was discontinued. Two weeks later standard growth hormone stimulation test with clonidine showed partially insufficient growth hormone secretion. During NS remission with normalization of thyroid function (TSH 6.680 mU/l, FT4 13.85 pmol/l) and normalization of IGF-1 level (132 mcg/l) partial catch-up growth was observed (height velocity increased from 3.5 cm/year to 7.3 cm/year, based on 4-month calculation period). Conclusions. Clinicians should be aware of a risk of developing hypothyroidism and consider thyroid function testing during the treatment of children with NS, as well as actively treat hypothyroidism and evaluate growth.